A dual‐stopband FSS using knitted and strong‐coupled structures with excellent angular stability and polarisation insensitivity. Issue 9 (1st June 2022) - Li, Chenchen; Yan, Mingbao; Wang, Weiyu; Wang, Jiafu; Xia, Song; Bai, Hui; Wang, He; Li, Songyan; Qin, Zhe; Qu, Shaobo
Abstract: In this paper, a novel dual‐stopband frequency selective surface (FSS) based on the knitted and strong‐coupled structures is proposed. The proposed FSS works stably at frequencies of 2.51 and 5.06 GHz for both TE and TM mode, even when the incident angles vary from 0° to 75°. The element size and thickness of the proposed structure are λ 0 /16 and λ 0 /170, respectively, where λ 0 represents the free‐space wavelength. To clarify the operating principle, a general equivalent circuit model (ECM) is developed. A prototype of the proposed FSS is fabricated and measured. It is demonstrated that the proposed structure has good angular stability, polarisation insensitivity, and independent operation in the dual‐stopband. Importantly, the proposed structure has good prospects for application in dual‐band electromagnetic shielding in complex environments.